Twin pregnancies: incidence and outcomes in a tertiary health centre of Uttarakhand, India - Upreti, Purnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The frequency of twin pregnancies varies among different regions, countries and populations mostly due to the variation in dizygotic twinning. Twin pregnancy is associated with adverse maternal and fetal outcomes. This study was aimed to find out the frequency and outcome of twin pregnancies in a tertiary health centre of Uttarakhand. Methods: This is a retrospective hospital record-based study of the twin deliveries (with gestational age of 28 weeks and above) which took place in a tertiary health care centre of Uttarakhand from January 2016 to December 2017. Data regarding age, parity and registration status of women who delivered twins, factors associated with twin pregnancy, gestational age, fetal presentation, mode of delivery, pregnancy complications and neonatal outcome was collected and analyzed. Results: The frequency of twin pregnancy was found to be 1 in 52 pregnancies or 1.9%. Majority (56.4%) of the participants were in the age group of 21-25 years. 52.8% were multipara. 74.3% were unbooked. 3.7 % conceived after ovulation induction and 8.2% had family history of twins. Pre-term labour (58.3%) was the most common complication followed by malpresentation (around 37%). Cephalic-cephalic was the commonest fetal presentation (43.8%).58.3% neonates were premature at birth and 83.4% had low birth weight. Male-male was the commonest sex combination of twin pair (30.4%) followed by female-female (28.6%). Conclusions: Twin pregnancy is a high-risk pregnancy associated with adverse maternal and fetal outcomes.